Estimativas das radiações direta e difusa em superfícies inclinadas com base na razáo de insolação - De Souza, Adilson P. (2013)
Statistical equations were obtained and evaluated with annual, seasonal and monthly data groupings for estimates of direct and diffuse components of solar radiation based on the sunshine duration (ratio of sunshine and photoperiod) incident on horizontal and inclined surfaces to 12.85, 22.85 and 32.85° with facing to North, in Botucatu, SP. The ratios between the two components and radiation at the top of the atmosphere were used, in a database whose inclinations were measured in three different periods (22.85°: 04/1998 to 07/2001; 12.85°: 08/2011 to 02/2003; and 32.85°: 03/2003 to 12/2007) and concomitant with horizontal measures and sunshine duration. The correlations showed a linear and second degree polynomial behavior for the direct and diffuse radiation, with higher coefficients of determination in periods of low variation in the coverage of the sky (cloudiness). The highest values of the direct and diffuse radiation were found in winter and summer, respectively for all surfaces evaluated. The increase in the inclination angle decreased the performance of equations in all groups of data with increase in scattering and decrease in index of the adjustment, however, the monthly equations allowed better performance for the two components.